PENGARUH BIAYA LINGKUNGAN, LEVERAGE, UKURAN DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR AGRICULTURAL PRODUCT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2024). - Siti Mudrikah; Anissa Amalia Mulya (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the influence of environmental costs, leverage, firm size, and liquidity on financial performance (an empirical study on agricultural product sub-sector companies listed on the indonesia stock exchange for the period 2021-2024). The research method used was secondary data obtained from companies’ annual reports. Samples were selected using purposive sampling based on specific criteria, and data were analyzed using multiple linear regression. The results show that leverage has a significant negative effect on financial performance. Meanwhile, environmental costs, size, and liquidity have no effect on financial performance.